2014
DOI: 10.1117/12.2060810
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in laser ablation modelling for asteroid deflection methods

Abstract: Over the past few years, a series of studies have demonstrated the theoretical benefits of using laser ablation in order to mitigate the threat of a potential asteroid on a collision course with earth. Compared to other slow-push mitigation strategies, laser ablation allows for a significant reduction in fuel consumption since the ablated material is used as propellant. A precise modelling of the ablation process is however difficult due to the high variability in the physical parameters encountered among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Note that in the case volume absorption is considered, the temperature peak is located under the surface, as explained by Anisimov and Luk'yanchuk (2002). Thiry and Vasile (2014) reported that the correlated color temperature recorded from the light emitted by the ablation spot with a Nd:YAG laser was consistent with the temperature predicted by the model assuming surface absorption. In the remaining, we thus carry on with the assumption that the material is a surface absorber at the laser wavelength.…”
supporting
confidence: 55%
“…Note that in the case volume absorption is considered, the temperature peak is located under the surface, as explained by Anisimov and Luk'yanchuk (2002). Thiry and Vasile (2014) reported that the correlated color temperature recorded from the light emitted by the ablation spot with a Nd:YAG laser was consistent with the temperature predicted by the model assuming surface absorption. In the remaining, we thus carry on with the assumption that the material is a surface absorber at the laser wavelength.…”
supporting
confidence: 55%
“…Especially for ground-based laser systems, a short deflection time is almost invalid due to the duration of irradiation to the asteroid. Thiry et al presented a new 3D thermal model of the laser ablation applied to the deflection of an asteroid, in order to calculate the efficiency of a laser deflection system [17]. They calculated that the coupling efficiency of a high-energy laser can reach 80 N s / J μ ⋅ theoretically.…”
Section: Introductionmentioning
confidence: 99%